Organisms-on-a-chip - Raimondi Manuela Teresa (EPJ Web of Conferences)
The progression of fibrosis is frequently related to a failed healing process, and it may affect many tissues and organs causing severe consequences including post-infarct heart insufficiency, post-injury limb paralysis, cirrhosis, nephropathy, retinopathy, failure of implanted devices and even resistance to chemotherapy in solid tumours. Experimental models, both in vitro and in vivo, are widely used for studies of basic pathophysiology, and for pre-clinical testing of pharmacological therapies counteracting fibrosis. However, conventional models are not able to realistically reproduce the revascularization aspect of the inflammatory reaction that leads to the generation of fibrotic tissue. In this talk, I will present the most advanced frontier in this sector, represented by the new concept of an “organism-on-a-chip”. This is a hybrid model, in which an organ-on-a-chip is implanted sub-cute in a living organism, such as a mouse or an embryonated avian egg, thus eliciting a foreign-body reaction with the formation of a fibrotic microenvironment. In an organism-on-a-chip, the fibrotic reaction can be guided using microscopic scaffolds incorporated in the implanted chip. The fibrotic microenvironment can then be imaged longitudinally, in high resolution, in single and multiphoton optical microscopy, with the added advantage of significantly reducing animal sacrifice. The optical measurements performed in the platform address parameters of the extra-cellular matrix (stiffness, collagen density, collagen orientation, coefficient of diffusion) and vascularity (number of blood vessels, length, blood velocity and vessel permeability).